First comparative results about the direct effect of traditional cigarette and e-cigarette smoking on lung alveolocapillary membrane using dynamic ventilation scintigraphy. Issue 2 (February 2019) - Barna, Sandor; Rózsa, David; Varga, Jozsef; Fodor, Andrea; Szilasi, Maria; Galuska, Laszlo; Garai, Ildiko
Abstract : Introduction: Dynamic inhalation scintigraphy (DIS) with technetium-99m-diethylenetriamine-pentaacetate aerosol is a useful nuclear medicine procedure for staging and monitoring the damage of alveolocapillary membrane. The e-cigarette is a new popular smoking device producing vapor from the nicotine solution. Many studies have shown that e-cigarettes appear to be safer than smoking, but there are still debates to what extent e-cigarettes are less harmful than smoking. In this prospective, self-controlled study, we compared DIS results among volunteers smoking an e-cigarette and their results after they returned to traditional cigarette smoking for a week. Participants and methods: We included 24 healthy volunteers into this study who regularly used e-cigarette containing at least 10 mg nicotine/ml. We performed baseline DIS study in volunteers with e-cigarette smoking and then we asked them to return to traditional cigarette smoking for a week. Conventional respiration tests were also measured. We statistically analyzed the effect of traditional cigarette on clinical parameters and pulmonary clearance of the radiopharmacon. Results: There was no significant change in the parameters of peak expiratory flow rate and Tiffeneau-Pinelli index respiration tests; forced vital capacity and forced expiratory volume in 1 s slightly decreased ( P <0.05), whereas the exhaled CO and COHb levels were significantly higher at traditional cigarette use ( P <0.0001), and increased in every case. The pulmonary clearance was significantly faster at traditional cigarette smoking compared with e-cigarette use ( P <0.0001). Conclusion: On the basis of our results, we suppose that e-cigarette smoking is less harmful to the lung function than a traditional cigarette, and it can be recommended to heavy smokers who are unable to stop smoking.